Ideology and meaning in ritual lexicons: A dialectical eco-linguistic analysis of the Teing Hang Woja text in the Manggarai speech community - Daar, Gabriel Fredi; Gunas, Tobias (Universitas Ahmad Dahlan, 2025)
Ritual language in Manggarai holds profound cultural-ecological significance, as it encodes collective values, environmental wisdom, and human–nature interdependence. Yet, despite eco-linguistic concerns over how language shapes and reflects ecological relationships, the lexicons of Teing Hang Woja have not previously been examined through this perspective. This study aims to describe the ideology and meaning of lexicons used in the ritual text of the teing hang woja in the speech Community of Manggarai, Flores Indonesia. This study also aims to describe the shift in the lexicons in the text as a result of changes in people's social activities. This is qualitative research with a phenomenological approach. Data were collected through interviews, participative observation, and Focus Group Discussion. Ten key informants were selected for interviews and FGD needs with several criteria. The results showed that the lexicons in the ritual text of teing hang woja contained the ideology of asking for an abundance of water, smoothness, and success of the agricultural process which were closely related to the socio-cultural conditions of the people as farmers. However, along with the social development of the community, the ideology contained in the text then expanded to other aspects such as the pleading for the success of the livestock business, education, and public health of the speakers. Meanwhile, the meaning contained in the text is more about stylistic meaning, affective meaning, social and reflective or spiritual meaning. The lexical analysis in Teing Hang Woja text not only provides insights into Manggarai's cultural ecology but also enriches eco-linguistic studies, emphasizing the importance of understanding language in efforts to safeguard ecological sustainability.